Brown over black : race and the politics of postcolonial citation - Burton, Antoinette M. (Three Essays Collective, 2012)
Recent attention to the urgency of economic and political cooperation between the Indian government and African states – often termed south-south globalization – suggests that the time has come for more critical histories of “Afro-Asian solidarity” than are presently available. That term, which gained currency at the famous meeting of over two dozen Third World representatives in Bandung, Indonesia, in 1955, refers to the story of affinities and exchanges between people of African and South Asian descent from ancient times to the present. More recently, it has enjoyed popularity as a metaphor for the fraternal connections between ex-colonial people in the wake of decolonization, when Africans and Indians (and others) joined forces to create a non-aligned movement in the Cold War world dominated by the USA and the USSR. This book tracks the racial hierarchies that were often at work in the lived experience and the geopolitical imaginaries of men and women for whom the ideals of Afro-Asian solidarity posed a genuine challenge. It also takes gender and sexuality as indispensable categories in the history of postcolonial India in/and the world. Drawing on the writings of the Ansuyah R. Singh, Frank Moraes, Chanakya Sen and Phyllis Naidoo, ‘Brown over Black’ reframes post-1947 Indian history in a set of Afro-Asian contexts, asking what the ideological and material work of race has been in shaping both geopolitical alliances and diasporic Indian histories.